Queer Velocities : Time, Sex, and Biopower on the Early Modern Stage - Row, Jennifer Eun-Jung (Book collections on Project MUSE., 2021)
"This book explores the sensations of haste and delay as represented in seventeenth-century French theater. Jennifer Eun-Jung Row proposes that these disruptive velocities--occasions when the tempos of desire subverted society's rhythms and norms--sparked new queer attachments and intimacies"--